Estimation of realized rates of genetic gain and indicators for breeding program assessment - Rutkoski, J.E. (Wiley, 2019)
Routine estimation of the rate of genetic gain (ΔGt) realized by a breeding program has been proposed as a means to monitor its effectiveness. Several methods of realized ΔGtestimation have been used in other studies, but none have been objectively evaluated in a plant breeding context. Stochastic simulations of 80 rice (Oryza sativaL.) breeding programs over 28 yr were done to generate data used to evaluate five methods of realized ΔGtestimation in terms of error, precision, efficiency, and correlation between true and predicted annual mean breeding values. Two indicators of ΔGt, the expected ΔGt, and the average number of equivalent complete generations (EqCg), were described and evaluated. At best, estimates of realized ΔGtwere over or underestimated by 15 and 27% when considering all 28 yr and the past 15 yr of breeding, respectively. The best methods were the estimated breeding value, control population, and era trial methods. Among these, correlations between true and estimated ΔGtwere at best 0.59, indicating that these methods cannot very accurately rank breeding programs in terms of realized ΔGt. The expected ΔGtand the average EqCg were shown to be useful indicators for determining if a nonzero genetic gain is expected. Determining which of the three best realized ΔGtestimation methods evaluated, if any, would be appropriate for any given breeding program should be done with careful consideration of the objectives, resources, seed stocks, and structure of the data available.